Определение методом индентирования пригодности известняков для изготовления контейнеров аппаратов высокого давления - Виноградов, С.А.; Доценко, В.М.; Сороченко, Т.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The indentation method to test the mechanical properties of the material of the container for high pressure apparatus has been described. The proposed method allows to determine in situ the destructiveness of the container under synthesis conditions. The complex characteristic of the elastic and plastic properties of the material has been proposed and relation between the proposed characteristic and the destructiveness of the container’s material has been found.